Collagen fleece in orthopaedic infections - Susan M. Ge, MD; Edward J. Harvey, MD (OTA International, 2021)
Abstract. Collagen fleece is a relatively new development. It represents another option in the battle against infection. It is a cheap, biocompatible, and resorbable local antibiotic delivery mechanism with favorable drug release kinetics and low risk of adverse effects or toxicity. Benefit may be conferred when used in contaminated cases. Significantly more research is still needed before the adoption of collagen fleece as the standard of care. However, we can likely conclude that there are no major adverse effects and it can be safely used as an adjunct in addition to conventional therapies for the prophylaxis and treatment of infections.